Alcohol-induced risky sexual behavior among socially anxious drinkers. (3rd September 2017) - Terlecki, Meredith A.; Richter, Ashley A.; Neighbors, Clayton; Young, Chelsie M.; Buckner, Julia D.
Abstract: Heavy college drinking is associated with risky sexual behavior. It is therefore important to identify groups that are especially vulnerable to alcohol-influenced sexual risk (e.g., unplanned/unexpected sex). Undergraduates with elevated social anxiety represent one such vulnerable group given that social anxiety is associated with fear of intimacy and heavier drinking in intimate situations and situations with expected negative affect. Drinking to cope with negative affect induced by fear of intimacy might render socially anxious undergraduates vulnerable to risky sexual behavior, yet no known studies have examined this relationship. The current study tested whether social anxiety was related to alcohol-related sexual behaviors among current (past-month) drinking undergraduates (88.1% female; 77.6% non-Hispanic Caucasian) with higher (i.e., clinically elevated) social anxiety (HSA; n = 40) or lower (more normative) social anxiety (LSA; n = 94). Coping motives were examined as a moderator of the social anxiety-risky sexual behavior relationship. Gender was a covariate. HSA students reported more frequent alcohol-influenced sexual risk including regretted sexual situations, unprotected sex, sex with unwanted partners, unwanted sex, pressured/forced to have sex, and pressured someone to have sex. Coping motives significantly interacted with social anxiety group in the prediction of risky sexual behaviors except regretted sexual situations, such that HSA students with greater coping motives experienced more frequent sexual risk when drinking. Findings indicate that HSA students may be particularly vulnerable to risky sexual behaviors and suggest that coping motivated drinking may be an important target for therapeutic interventions geared toward reducing risky sexual behaviors among this high-risk population.